2005
DOI: 10.1002/hep.20484
|View full text |Cite
|
Sign up to set email alerts
|

Liver tissue engineering at extrahepatic sites in mice as a potential new therapy for genetic liver diseases

Abstract: Liver tissue engineering using hepatocyte transplantation has been proposed as an alternative to whole-organ transplantation or liver-directed gene therapy to correct various types of hepatic insufficiency. Hepatocytes are not sustained when transplanted under the kidney capsule of syngeneic mice. However, when we transplanted hepatocytes with the extracellular matrix components extracted from Engelbreth-Holm-Swarm cells, hepatocytes survived for at least 140 days and formed small liver tissues. Liver engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
129
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 34 publications
7
129
1
Order By: Relevance
“…The method for hepatocyte isolation and purification is based on a modification of procedures reported by active regeneration potential (18). We also demonstrated these tissues were able to support human-specific hepatiBerry and Friend (2) and reported previously (3, 16,18).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The method for hepatocyte isolation and purification is based on a modification of procedures reported by active regeneration potential (18). We also demonstrated these tissues were able to support human-specific hepatiBerry and Friend (2) and reported previously (3, 16,18).…”
Section: Introductionsupporting
confidence: 67%
“…including hepatocyte transplantation and liver tissue engineering, have been highlighted (12,13 the area of the body other than the liver, such as under MATERIALS AND METHODS the kidney capsule space or mesenteric leave) can also Experimental Animals have therapeutic efficacy (6,10,13,17). However, this approach results in short-term survival of the transAll animal studies used the institutional guidelines set forth by Stanford University and Nara Medical Univerplanted hepatocytes (13,17,18). A number of modifications in the transplantation setting, such as genetic transsity Animal Care Committees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the marker protein of the transplanted hepatocytes, hAAT, demonstrates a short half-life (less than 2 hours) in the mouse 7 and is produced only from the hepatocytes, the viability and survival of the transplanted hepatocytes in vivo can reasonably be assessed by periodic mouse serum measurement of the hAAT reporter protein, as described previously. [3][4][5][6][7] Mice were sacrificed at day 140; the grafts were excised and processed for histological examination.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 We recently reported that the inefficient hepatocyte survival may be overcome by providing ECMs extracted from murine Engelbreth-Holm-Swarm tumor cell lines (EHS-ECMs). [3][4][5][6] The EHS-ECMs are rich in ECM components, predominantly laminin and type IV collagen, but also contain a small amount of growth factors, such as epidermal growth factor. This study was performed to determine the effects of EHS-ECMs on hepatocyte survival and whether it was solely due to ECMs or to a combination of ECMs and growth factors in EHS-ECMs.…”
mentioning
confidence: 99%